A content-based retrieval system for blood cells images - Seng, W.C.; Mirisaee, S.H. (2009)
Content-based image retrieval techniques have extensively been studied for past few years. However; few systems are dedicated to medical images today while demands for content-based analysis and retrieval tools increases with growth of digital medical image databases. A prototype of content-based image retrieval system is built to investigate performance of descriptors for blood cell image retrieval. Here, traditional global color histogram and wavelet-based method is investigated. In addition, performance of indexing method for the aforementioned descriptors is analyzed. The prototype system allows users to search by providing a query image and selecting one of four implemented methods. Research goal is enhancing current content-based image retrieval techniques. Proposed method is able to perform clinically relevant queries on image databases without user supervision.